Antioxidative Stress Mechanisms behind Resveratrol: A Multidimensional Analysis - Tongyu Gu; Nianmin Wang; Tong Wu; Qi Ge; Liang Chen (Journal of Food Quality)
Over the past decade, oxidative stress was shown to be a key factor for various diseases. The term “antioxidant” also rapidly gained attention worldwide, viewed as beneficial in disease prevention. Resveratrol (RSV), a natural polyphenol, is a plant antitoxin formed in response to harmful environmental factors such as infection and injury. This antitoxin is found in grapes, strawberries, peanuts, or herbal medicines and exhibits many pharmacological effects involved in antitumor, anti-inflammatory, antiaging, and antioxidation stress mechanisms. Recently, numerous in vitro and in vivo experiments have shown that RSV harbors antioxidative stress properties and can be used as an antioxidant. Here, we review the free radical scavenging ability, antioxidant properties, signaling pathways, expression and regulation of antioxidant enzymes, and oxidative stress-related diseases associated with RSV.